Adequacy between higher education supply and employers' needs (in the rural area) - Ferreira, F.; Basílio, M. S. B.; Teixeira, F. J. C. S. N. (Egitania Sciencia, 2009)
Based on the present economic context and considering the Bologna Process requisites, the main goal of this study is to determine whether the higher education training offered, in Lower Alentejo, meets the employers’ needs and/or technical interests. In the first phase of the study, inquisition techniques are used to characterize the technical needs of the Region’s employers. Subsequently, the results obtained are compared to identify corrective actions and/or to formulate restructuring guidelines and suggestions for improvement.